Comparative Evaluation of Orthostatic Hypotension in Patients with Diabetic Nephropathy - Gamze Aytaş; Rümeyza Kazancıoğlu; Ömer C. Elçioğlu; Meltem Gürsu; A. Serra Artan; Ayşegül Yabacı; Pinar Soysal; Kadir Bilgi; Semra Özçelik (Karger Publishers, 2021)
Introduction: Orthostatic hypotension (OH) affects 5-20% of the population. Our study investigates the presence of OH in diabetic nephropathy (DNP) patients and the factors affecting OH in comparison with nondiabetic chronic kidney disease (NDCKD) patients. Method: Patients presented to the nephrology clinic, and those who consented were included in the study. DNP was defined by kidney biopsy and/or clinical criteria. NDCKD patients of the same sex, age, and eGFR were matched to DNP patients. Demographic parameters and medications were obtained from the records. OH was determined by Mayo clinic criteria. The same researcher used an electronic device to measure blood pressure (BP). All samples were taken and analyzed the same day for biochemical and hematologic parameters and albuminuria. Results: 112 (51 F, 61 M, mean age: 62.56 ± 9.35 years) DNP and 94 (40 F, 54 M, mean age: 62.23 ± 10.08 years) NDCKD patients were included. There was no significant difference between DNP and NDCKD groups in terms of OH prevalence (70.5 vs. 61.7%, p = 0.181). Male patients had significantly higher OH prevalence than female patients (74.7 vs. 60.0%, p = 0.026). There was no significant difference in change in systolic BP between the groups (24.00 [10.00-32.00] mm Hg vs. 24.00 [13.75-30.25] mm Hg, p = 0.797), but the change in diastolic BP was significantly higher in the DNP group (8.00 [2.00-13.00] mm Hg vs. 6.00 [2.00-9.00] mm Hg, p = 0.025). In the DNP group, patients with OH had significantly higher uric acid levels than those without OH (7.18 ± 1.55 vs. 6.36 ± 1.65 mg/dL, p = 0.017). And, 73.7% of patients on calcium channel blockers developed OH (p = 0.015), and OH developed in 80.6% of 36 patients on alpha-blockers (p = 0.049). Conclusion: OH prevalence is very high in CKD, and etiology of CKD does not have a statistically significant effect on the frequency of OH, despite a difference that could be meaningful clinically. Therefore, patients with CKD are checked for OH, with or without concurrent diabetes mellitus. Evaluation of postural BP changes should be a part of nephrology practice.